PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi kasus pada Karyawan Departemen Spinning I PT. DAMATEX Salatiga) The Influence of Motivation and Discipline of work to Employee Performance of Spinning I Department of PT. DAMATEX Salati - Adityasa Nugraha; Hari Susanta Nugraha; Andi Wijayanto (Universitas Diponegoro, 2013)
PT. Damatex Salatiga is a company that runs in the field of textiles oriented on profit goals and strive to create competitive advantages. Employee performance is one of measurements, which is often used in determining the effectiveness of the company. A company will not able to improve if the performance of employees is stagnant, nevertheless with the high level of competition in the business world. In order to improve employees performance by increasing motivation and discipline of work. The purpose of this research is to investigate and examine the effect of the motivation and discipline of work to employee performance of Spinning I Department of PT. Damatex Salatiga.This research uses explanatory research approach of 72 repondents that taken with proportionate random sampling method. Data collection techniques is using questionnaires, interviewed and the documentation technique. Data were analyzed using linear regression analysis.Based on the results of the analysis, it shows that motivation has a positive effect toward performance about 14,5%. Employees discipline has a positive effect toward performance about 12,7%.Motivation and discipline have a significant effect toward performance about 19,8%. The higher level of motivation and discipline of work, the higher level of performance.Advice that can be given to the company is the company should be focus on labours by making some reviews of work assignments that have been established and need to be adjust between job assignment with capability of workers. Company should give a spirirt by giving appreciation for theworkers and if possible, recreation program for the workers, thus eventually will improve the performance of their workers.